Nonoscillatory Solutions for System of Neutral Dynamic Equations on Time Scales - Zhanhe Chen; Taixiang Sun; Qi Wang; Hongjian Xi (The Scientific World Journal)
We will discuss nonoscillatory solutions to the n-dimensional functional system of neutral type dynamic equations on time scales. We will establish some sufficient conditions for nonoscillatory solutions with the property limt→∞⁡xit=0,   i=1, 2, …,n.